Identifikasi Dan Prevalensi Babesia sp. Pada Anjing Lokal Di Kecamatan Kelapa Lima Dan Kecamatan Maulafa, Kota Kupang - Kefin Elyzabeth Tahun; Aji Winarso; Julianty Almet (Jurnal Veteriner Nusantara, 2022)
Canine babesiosis is a disease caused by infection with Babesia spp. Babesia attack erythrocyte and caused health problem, from mild anemia and fatality in severe infected dogs. Remembering the importance of dog as a animal in Kupang City society, the epidemiological data on Canine Babesiosis are important for control measure development. This research aims to identify blood parasite and to determine the prevalence of Babesiosis in local dog breed in Kupang City. A total of 60 blood samples were collected from Maulafa Subdistrict and Kelapa Lima Subdistrict, Kupang City, East Nusa Tenggara. The animal signalments and health histories were obtained by observation and structured interview by questionnaire. Collected data were analyzed descriptive. The results showed that 11 out of 60 dogs (18,3%) were infected by Babesia sp. The occurrence of Babesia sp. was related to environmental condition supporting it’s vector life cycle (Rhipicephalus sanguineus).